High-capacity coating layer composite graphite material for lithium ion battery and preparation method of high-capacity coating layer composite graphite material
By using a step-by-step feeding fusion process combining amorphous carbon and anthracite in lithium-ion batteries, a composite graphite coating structure is constructed, which solves the problem of insufficient capacity and circulation performance of graphite materials, and achieves high capacity and stable circulation coating The composite graphite layer increases the energy density and cycle life of lithium-ion batteries.
Patent Information
- Application Number
- CN202411262536.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Existing graphite materials have low gram capacity or poor circulation performance in lithium-ion batteries, making it difficult to meet the needs of high energy density and long cycle life.
Using a step-by-step feeding fusion process for combining amorphous carbon and anthracite, a composite graphite coated structure with natural graphite as the substrate and covered with anthracite particles and a coated carbon layer is constructed. The composite graphite coated structure is heated by asphalt, resin or tar as coating agent. Plastic shaping, pre-carbonization and graphitization treatment form a high-capacity, cyclic stable clad composite graphite material.
It effectively improves the lithium storage capacity and electrolyte compatibility of the material, solves the problems of low artificial graphite capacity and poor circulation stability of natural graphite, and realizes a high-capacity, cyclic stability of clad composite graphite material.
Smart Images

Figure CN119118117A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion negative electrode materials, and in particular to a high-capacity coating layer composite graphite material for a lithium ion battery and a preparation method thereof. Background Art
[0002] As one of the important energy storage devices, lithium-ion batteries have many advantages such as high energy density, long cycle life, environmental friendliness and high safety. They can provide energy for portable electronic devices and new energy vehicles, and have achieved great success in the field of energy applications. As people's requirements for the performance of lithium-ion battery products continue to increase, the performance requirements for negative electrode materials are becoming more and more stringent, which continuously promotes breakthroughs in material research and development innovation.
[0003] Graphite materials are currently the most widely used negative electrode materials for lithium-ion batteries due to their low cost advantages, abundant sources of raw materials, and layered structures suitable for lithium-ion extraction / embedding. Graphite materials are mainly divided into artificial graphite and natural graphite. Artificial graphite has a stable structure, excellent rate performance, and good electrolyte compatibility, but its gram capacity is relatively low, which makes it difficult to meet today's increasingly high energy density requirements; while natural graphite has a large lamellar structure, a high gram capacity, and good processing performance, but due to its many structural defects, its cycle performance is poor, and a single use cannot meet the long cycle life currently required. Therefore, more design and development solutions are still needed for high-capacity, cycle-stable graphite negative electrode materials. Summary of the invention
[0004] In order to solve the problem that the above-mentioned existing artificial graphite has relatively low specific capacity and natural graphite has many structural defects, resulting in poor cycle performance, the present invention provides a high-capacity coating layer composite graphite material for lithium-ion batteries and a preparation method, combining the material properties of artificial graphite and natural graphite, using amorphous carbon and anthracite, combined with a step-by-step feeding and fusion process, effectively controlling the construction of a composite graphite coating structure with natural graphite as the matrix, anthracite particles and a coating carbon layer on the surface, effectively improving the lithium storage capacity of the material, and improving the compatibility between the material and the electrolyte, to develop a high-capacity, cycle-stable coating layer composite graphite material.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery, characterized in that it comprises the following steps: S1. Select high-quality anthracite and grind it to obtain anthracite fine powder as coating material A; select natural graphite as base material B; use one or a combination of asphalt, resin, tar as coating agent C; mix A, B, C in a mass ratio of (20-40): (40-80): (8-30); S2, firstly mix the coating material A and the coating agent C thoroughly, and then heat to 50-500°C to fuse until the liquid phase is evenly dispersed; S3, adding the matrix material B to the liquid phase dispersion in step S2 in batches, controlling the fusion temperature curve and the dispersion frequency, and obtaining a composite graphite precursor with a surface coating layer; S4, subjecting the composite graphite precursor obtained in step S3 to shaping, pre-carbonization, graphitization, screening and demagnetization processes to obtain a coating layer composite graphite material.
[0006] Preferably, the asphalt includes any one or a combination of at least two of natural asphalt, petroleum asphalt, shale asphalt and carbon fiber asphalt; The resins include any one or a combination of at least two of phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin and furfural resin; The tars include any one of coal tar, ethylene tar, bio-oil and grease pyrolysis tar, or a combination of at least two of them.
[0007] Preferably, in the step (1), the particle size D50 of the anthracite fine powder is 1 to 4 μm; the particle size D50 of the matrix material B is 10 to 16 μm; and the particle size D50 of the coating agent C is 1 to 8 μm.
[0008] Preferably, the coking value of the coating agent C in step (1) is 10 to 80%.
[0009] Preferably, in step (3), the proportion of matrix material B added in batches is set to 5-30%.
[0010] Preferably, in step (3), the fusion temperature is controlled to be 50-500° C., the holding time is 0.5-4 h, and the dispersion frequency is controlled to be 1-50 Hz.
[0011] Preferably, in step (4), the pre-carbonization treatment temperature is 500° C. to 1300° C., the heating rate is 5 to 10° C. / min, and the carbonization treatment time is 2 to 4 h.
[0012] Preferably, the graphitization temperature in step (4) is set to 2800-3200°C.
[0013] Preferably, in the step (4), the particle size D50 of the composite graphite material in the coating layer is 10 to 20 μm.
[0014] The present invention also provides a high-capacity coating layer composite graphite material for a lithium ion battery, characterized in that the high-capacity coating layer composite graphite material is prepared by the above-mentioned preparation method.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts high-quality anthracite fine powder as coating material, effectively reducing material costs, combining the material properties of artificial graphite and natural graphite, using amorphous carbon and anthracite, and combining the step-by-step feeding and fusion process to effectively control the construction of a composite graphite coating structure with natural graphite as the matrix material, anthracite particles and a coating carbon layer covered on the surface, effectively improving the lithium storage capacity of the material, the reaction interface between the anthracite particle coating material and the electrolyte is completely superior to the reaction interface between the matrix material and the electrolyte, improving the compatibility between the material and the electrolyte, solving the problems of low specific capacity of artificial graphite and poor cycle stability of natural graphite, thereby developing a high-capacity, cycle-stable coating layer composite graphite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 : SEM image of the composite graphite material of the coating layer in Example 2 of the present invention; Figure 2 : SEM image of the composite graphite material of the coating layer of Example 3 of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0018] S1. Weigh 25kg of high-quality anthracite and crush it to obtain anthracite fine powder with a D50 of 2μm as coating material A; weigh 50kg of natural graphite with a D50 of 11μm as base material B; weigh 15kg of natural asphalt with a D50 of 2μm and a coking value of 50% as coating agent C; S2, first put all the coating material A and the coating agent C into the reaction kettle and mix them evenly, then heat and stir to 300°C to blend until the liquid phase is evenly dispersed; S3, adding the matrix material B to the liquid phase dispersion in step S2 in batches, adding 10% each time, controlling the fusion temperature curve and the dispersion frequency, to obtain a composite graphite precursor with a surface coating layer; Preferably, in step (3), the fusion temperature is 300° C., the holding time is 2 h, and the dispersion frequency is controlled to be 30 Hz.
[0019] S4. The composite graphite precursor obtained in step S3 is shaped, and then placed in a carbonization furnace for pre-carbonization treatment, the pre-carbonization treatment temperature is 800°C; the carbonization treatment time is 3 hours, and then placed in a graphitization furnace for graphitization treatment at 3000°C, and the graphitized material is sieved and demagnetized to obtain a coating layer composite graphite material with a D50 of 14.72μm. Example
[0020] S1. Weigh 35kg of high-quality anthracite and crush it to obtain anthracite fine powder with a D50 of 2.5μm, which is the coating material A; weigh 70kg of natural graphite with a D50 of 12.3μm as the base material B; weigh 20kg of epoxy resin with a D50 of 5μm and a coking value of 30% as the coating agent C; S2, first put all the coating material A and the coating agent C into the reaction kettle and mix them evenly, then heat and stir to 150°C to blend until the liquid phase is evenly dispersed; S3, adding the matrix material B to the liquid phase dispersion in step S2 in batches, adding 20% each time, controlling the fusion temperature curve and the dispersion frequency, to obtain a composite graphite precursor with a surface coating layer; Preferably, in step (3), the fusion temperature is controlled to be 150° C., the holding time is 1.5 h, and the dispersion frequency is controlled to be 40 Hz.
[0021] S4. The composite graphite precursor obtained in step S3 is shaped, and then placed in a carbonization furnace for pre-carbonization treatment, the pre-carbonization treatment temperature is 1000°C; the carbonization treatment time is 2.5 hours, and then placed in a graphitization furnace for graphitization treatment at 2900°C, and the graphitized material is sieved and demagnetized to obtain a coating layer composite graphite material with a D50 of 15.26 μm.
[0022] like Figure 1 Shown is the SEM image of the composite graphite material of the coating layer in Example 2. Example
[0023] S1. Weigh 35 kg of high-quality anthracite and crush it to obtain anthracite fine powder with a D50 of 3.5 μm, which is the coating material A; weigh 80 kg of natural graphite with a D50 of 15 μm as the base material B; weigh 25 kg of a combination of carbon fiber pitch and coal tar with a D50 of 8 μm and a coking value of 40% as the coating agent C; S2, first put all the coating material A and the coating agent C into the reaction kettle and mix them evenly, then heat and stir to 250°C to blend until the liquid phase is evenly dispersed; S3, adding the matrix material B to the liquid phase dispersion in step S2 in batches, adding 30% each time, controlling the fusion temperature curve and the dispersion frequency, to obtain a composite graphite precursor with a surface coating layer; Preferably, in step (3), the fusion temperature is controlled to be 240° C., the holding time is 2 h, and the dispersion frequency is controlled to be 40 Hz.
[0024] S4. The composite graphite precursor obtained in step S3 is shaped, and then placed in a carbonization furnace for pre-carbonization treatment, the pre-carbonization treatment temperature is 1250°C; the carbonization treatment time is 4 hours, and then placed in a graphitization furnace for graphitization treatment at 2800°C, and the graphitized material is sieved and demagnetized to obtain a coating layer composite graphite material with a D50 of 15.05 μm.
[0025] like Figure 2 Shown is the SEM image of the composite graphite material of the coating layer in Example 3.
[0026] Comparative Example 1: Using high-quality anthracite as raw material, through crushing, shaping, pre-carbonization, graphitization, screening, demagnetization and other processes, artificial graphite material with D50 of 14.51μm is obtained; Comparative Example 2: Taking natural graphite as raw material, the processes of crushing, impurity removal, purification, spheroidization, purification, screening, demagnetization and the like are carried out to obtain natural spherical graphite material with D50 of 14.66 μm.
[0027] Performance testing: 1. The negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were made into button batteries for performance testing: At room temperature, the obtained negative electrode material, dispersant CMC, conductive agent SP, and binder SBR were mixed evenly in pure water at a mass percentage of 96:1.5:1:1.5 to prepare a slurry; the slurry was evenly coated on the copper foil with a coating surface density of about 5 mg / cm 2 Then put the copper foil into a vacuum drying oven at 80℃ for 12 hours. Cut the dried copper foil into pieces with an area of 2cm 2 The working electrode was made of a disc; then it was assembled into a button cell in a vacuum glove box with a metal lithium sheet as the counter electrode, 1 mol / L LiPF6 / EC+DEC (volume ratio 1:1) electrolyte, and a PE separator. The assembled button cell was left at room temperature for 24 hours before the electrochemical test began. The test results are shown in Table 1.
[0028] 2. The negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were used to make lithium-ion full batteries for performance testing: The obtained negative electrode material, conductive agent SP, dispersant CMC, and binder SBR were dissolved in a solvent in a mass percentage of 94.5:1.5:2:2 and mixed to form a negative electrode slurry. The solid content was controlled at 40%, and the slurry was coated on a copper foil current collector and vacuum dried to obtain a negative electrode sheet. The compaction density of the negative electrode sheet was 1.50 g / cm 3 , single surface density is 10mg / cm 2 ; Then, the ternary positive electrode prepared by the traditional mature process, 1mol / L LiPF6 / EC+DMC+EMC (volume ratio 1:1:1) electrolyte, diaphragm, and shell are assembled into 18650 cylindrical single cells using conventional production processes. The assembled 18650 cylindrical single cells are tested for capacity retention rate at 25°C with 1C charge / 1C discharge cycles for 100 cycles. The test results are shown in Table 1 Table 1
[0029] As can be seen from Table 1, the first discharge capacity of the high-capacity coating layer composite graphite material prepared in Examples 1 to 3 of the present invention can reach 363 to 366 mAh / g, the first charge and discharge efficiency is ≥95.21%, and the capacity retention rate after 100 cycles of 1C charge / 1C discharge at 25°C is ≥96.72%, which are higher than those of Comparative Examples 1 and 2.
[0030] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-capacity coating composite graphite material for a lithium-ion battery, characterized in that: The following steps are involved: S1. Select high-quality anthracite and grind it to obtain anthracite fine powder as coating material A; select natural graphite as base material B; use one or a combination of asphalt, resin, tar as coating agent C; mix A, B, C in a mass ratio of (20-40): (40-80): (8-30); S2, firstly mix the coating material A and the coating agent C thoroughly, and then heat to 50-500°C to fuse until the liquid phase is evenly dispersed; S3, adding the matrix material B to the liquid phase dispersion in step S2 in batches, controlling the fusion temperature curve and the dispersion frequency, and obtaining a composite graphite precursor with a surface coating layer; S4, subjecting the composite graphite precursor obtained in step S3 to shaping, pre-carbonization, graphitization, screening and demagnetization processes to obtain a coating layer composite graphite material.
2. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: The asphalt includes any one of natural asphalt, petroleum asphalt, shale asphalt and carbon fiber asphalt, or a combination of at least two thereof; The resins include any one or a combination of at least two of phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin and furfural resin; The tars include any one of coal tar, ethylene tar, bio-oil and grease pyrolysis tar, or a combination of at least two of them.
3. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: In the step (1), the particle size D50 of the anthracite fine powder is 1 to 4 μm; the particle size D50 of the matrix material B is 10 to 16 μm; and the particle size D50 of the coating agent C is 1 to 8 μm.
4. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: The coking value of the coating agent C in the step (1) is 10 to 80%.
5. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: In the step (3), the proportion of matrix material B added in batches is set to 5-30%.
6. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: In the step (3), the fusion temperature is controlled to be 50-500° C., the insulation time is 0.5-4 hours, and the dispersion frequency is controlled to be 1-50 Hz.
7. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: The pre-carbonization treatment temperature is 500°C to 1300°C, the heating rate is 5 to 10°C / min, and the carbonization treatment time is 2 to 4h.
8. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: In the step (4), the graphitization temperature is set to 2800-3200°C.
9. The method for preparing a high-capacity coating layer composite graphite material for a lithium-ion battery according to claim 1, characterized in that: In the step (4), the particle size D50 of the composite graphite material in the coating layer is 10 to 20 μm.
10. A high-capacity coating composite graphite material for lithium-ion batteries, characterized in that: The high-capacity coating layer composite graphite material is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Long-cycle natural graphite-based modified composite material as well as preparation method and application thereof
CN111232971A
High-capacity, high-compaction and quick-charge composite graphite negative electrode material and preparation method thereof
CN111646466A
Graphite negative electrode material, preparation method thereof and lithium ion battery
CN114171738A
Preparation method of long-circulation lithium ion battery graphite negative electrode material
CN114883544A
Graphite-based composite negative electrode material and preparation method and application thereof
CN115347176A
